О механизме звуковых изменений - Степонавичюс, А. (Kalbotyra, 1976)
By the mechanism of sound change we mean the problems of causation and transition. This paper is devoted to problems of the latter type. At the outset, the possible sources on new phonemes are pointed out. New phonemes may arise through: (1) rephonologization of phonemes; (2) phonemization of allophones; (3) monophonemization of phonemic clusters; (4) diphonemization of a single phoneme into phonemic clusters; (5) borrowing. Of the problems of transition proper the problems of graduality, discreteness, regularity and structural reinterpretation are discussed.